PERAN LIFESTYLE MEMEDIASI HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK IPHONE OLEH GENERASI Z - Dewi, Kadek Risma Ayuningsih; Pramudana, Komang Agus Satria (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.10.TAHUN.2023, 2023)
The purchase decision is action taken by consumers to buy a product after making selection or evaluation of one of several alternatives or choices and after that doing concrete follow-up, namely purchasing the product that has been selected. iPhone as one of the well-known smartphone brands in the Indonesian market in facing competition must be able to develop and innovate to determine an effective strategy. The purpose of the study was to examine the role of lifestyle as a variable that mediates the effect of price on purchasing decisions for iPhone products in Denpasar with 120 respondents who have used iPhone products. Data was collected through the distribution of questionnaires. The analysis technique used is path analysis. Based on the results, lifestyle significantly mediates the relationship between price and purchasing decisions. Setting a high price and being seen as prestigious will result in a higher lifestyle, thereby increasing purchasing decisions. In this study, it can be explained that the iPhone has a high price followed by a high respondent's lifestyl  and very high purchasing decisions for the iPhone. results indicate that lifestyle is positively and significantly able to mediate price on purchasing decisions on iPhone products in Denpasar.